2017
DOI: 10.1055/s-0043-101694
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diet liberalization on bowel preparation for colonoscopy

Abstract: Background and study aims Dietary restrictions are integral to colonoscopy preparation and impact patient satisfaction. Utilizing split-dose, lower-volume polyethylene glycol 3350-electrolyte solution (PEG-ELS), this study compared colon preparation adequacy of a low-residue diet to clear liquids using a validated grading scale. Patients and methods This was a prospective, randomized, single-blinded, single-center non-inferiority study evaluating diet the day prior to outpatient colonoscopy. Subjects were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 19 publications
1
26
1
Order By: Relevance
“…Same with our findings, this study found LRD not only did not compromise the bowel preparation, but bettered patient tolerance as well. Remaining 32 was performed by Walter and colleagues used BBPS to assess the bowel preparation quality and supported LRD was not-inferior to CLD, in keeping with our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Same with our findings, this study found LRD not only did not compromise the bowel preparation, but bettered patient tolerance as well. Remaining 32 was performed by Walter and colleagues used BBPS to assess the bowel preparation quality and supported LRD was not-inferior to CLD, in keeping with our findings.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with a recent RCT. In a prospective, randomised, single-centre non-inferiority trial, Walter et al concluded that the LRD a day before colonoscopy was non-inferior to CLD for getting adequate bowel cleansing using a split-dose regimen 32. In our study, ADR was higher in the SDR+LDR versus SDR+CLD (34.7% vs 29.6%), but the results were not statistically significant, p=0.167.…”
Section: Discussioncontrasting
confidence: 77%
“…[ 10 , 11 ] Several studies have evaluated the efficacy of diet liberalization to LRD on the bowel preparation compared to CLD. [ 14 , 18 , 20 , 21 ] In these studies, diet liberalization did not adversely affect bowel preparations and improved patient willingness to repeat the bowel preparation and tolerability of preparation solutions. Still, data regarding the effect of regular diet (RD) on the bowel preparation is lacking and RD on the day before colonoscopy is not recommended yet.…”
Section: Discussionmentioning
confidence: 83%
“…Specifically, whole grains uptake was significantly associated with inadequate bowel preparation among forbidden food categories (fiber-rich vegetables, seaweeds, whole grains, and seedy fruits), even though statistical significance was disappeared in multivariable analysis. In literature review, data showing comparable outcome of LRD on the bowel preparation with CLD are easily available, [ 14 , 15 , 21 , 22 ] but studies evaluating the effect of RD are very limited. [ 17 , 18 , 23 ] Jung et al [ 17 ] showed similar rate of adequate bowel preparation between RD and CLD (83.3% vs 83.5%) in healthy outpatients, recommending RD avoiding fiber-rich foods as possible diet instructions prior to colonoscopy.…”
Section: Discussionmentioning
confidence: 99%